The Bystander Behavior (For Friends) Scale: Factor Structure and Correlation With Prior Victimization - Cascardi, Michele (Journal of interpersonal violence, 2021)
The Bystander Behavior (for Friends) Scale (BBS) offers a promising method of studying prosocial bystander behavior in the context of sexual assault and intimate partner violence. The underlying structure of the BBS has only been studied in the development sample, which was predominantly White and from one university in the Northeast region of the United States. This single sample raises questions about the replicability and generalizability of the factor structure. In addition, confirmatory factor analytic (CFA) methods, which are favored for binary data, were not used in the developmental sample. There also is limited research on individual characteristics that may relate to engagement in different types of bystander behavior. The primary aims of the current study were to (a) use CFA to evaluate the factor structure of the BBS in a sample of university undergraduates recruited from four universities and (b) test associations between prior victimization (general and family-specific) and BBS factors. University undergraduates (n = 556) from four U.S. universities comprised the sample. Weighted least squares CFA confirmed the original four-factor model of the BBS, namely, Risky Situations, Accessing Resources, Proactive Behaviors, and Party Safety. The Proactive Behaviors factor was positively associated with both general and family-specific prior victimization. The Risky Situations and Party Safety factors were positively associated with general prior victimization but were not associated with family-specific prior victimization. The Accessing Resources factor was not associated with either general or family-specific prior victimization. The BBS is multidimensional, and the factor structure is robust. The different associations between certain types of bystander behavior and prior victimization highlight the potential value in considering the BBS factors separately.